Harmoni dalam Bhinneka Tunggal Ika: Pancasila sebagai pilar persatuan umat beragama dan masyarakat multikultural - Dzakiyah, Farah; Najma, Nur Afifah; Nafazah, Halawatun (Maliki Interdisciplinary Journal, 2025)
The importance of maintaining harmony in an area, especially within the scope of the state, is an obligation that the people of Indonesia must carry out. Moreover, Indonesia consists of various tribes, races, religions, and intergroups that are unique. This is where Pancasila is present as a guideline for the life of the state and nation and becomes a glue between the differences that exist in Indonesia. This article was compiled using a qualitative research method of literature study that discovered the beauty of harmony between Pancasila and religious values, especially in the environment of religious people and multicultural society. The first precept, ‘Belief in One God’, shows that Indonesia recognizes God as the spiritual foundation of state life. However, it still provides freedom for every citizen to embrace and practice their respective religions. Pancasila has proven that all the values contained in it follow the values in religious teachings. Pancasila and religion are two different things but do not contradict each other. Here we will discuss an example of conflict as a challenge that occurs in the country and how in the end it is these values that will maintain the harmony of Bhinneka Tunggal Ika.